2007
DOI: 10.1590/s1806-37132007000100021
|View full text |Cite
|
Sign up to set email alerts
|

Teratoma do mediastino simulando derrame pleural no estudo radiológico do tórax

Abstract: Teratomas account for 8-13% of all mediastinal tumors. A 27-year-old patient presented with chest pain and dyspnea of prolonged evolution. A chest X-ray revealed near total opacification of the right hemithorax. On a tomography scan of the chest, a collection of heterogeneous fluid, with irregular borders and 10.1 x 11.7 cm in size, was seen in the pleura of the lower two-thirds of the right hemithorax but was not encroaching on any of the adjacent structures. Based on the hypothesis that these findings repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…But this case revealed that pleural effusion was caused by mature cystic teratoma. Although because of the similarity of the clinical and radiological characteristics, such misdiagnosis is understandable [7] but it can also delay the diagnosis and increase the costs of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…But this case revealed that pleural effusion was caused by mature cystic teratoma. Although because of the similarity of the clinical and radiological characteristics, such misdiagnosis is understandable [7] but it can also delay the diagnosis and increase the costs of treatment.…”
Section: Discussionmentioning
confidence: 99%